MODULE DEVELOPMENT IN CIVIC EDUCATION COURSES GRADE NINE JUNIOR HIGH SCHOOL - Rendy Yudha Pratama; Fitra Endi Fernanda; Salman Alfarisi Salimu (Sean Institute, 2022)
This research is a development research (R&D) which aims to develop learning media in the form of a printed module in Civic Education for the ninth grade of Junior High School, which consists of module elements, namely teacher guidelines, student activity sheets, worksheets, worksheet keys, test sheets. and lock the test sheet. The results of research and product development prove that the printed learning module for the ninth graders of junior high school is classified as good. This is proven by three stages of trials. Phase one trial by expert lecturers with a percentage of 69.30% with quite good criteria, supervisor II with a percentage of 80.17% with good criteria, supervisor I with a percentage of 78.28% with good criteria. The second stage of the trial is a small-scale trial with 6 teachers as respondents with a percentage of 85.25% good criteria. The last stage of the trial is a large-scale trial with 25 respondents in the ninth grade of junior high school with a percentage result of 88.72% with very good criteria.